PENERAPAN STANDAR OPERASIONAL PROSEDUR PENGGUNAAN PERALATAN DALAM MENINGKATKAN PELAYANAN FOOD PRODUCTION DI HOLIDAY INN RESORT BARUNA BALI - Made Semara Yoga Dwi Darma Yoga; I Putu Gede Parma (Jurnal Manajemen Perhotelan dan Pariwisata, 2026)
This study aims to analyze the implementation of Standard Operating Procedures (SOP) in the use of equipment in the Food Production department at Holiday Inn Resort Baruna Bali, as well as to evaluate its impact on service quality improvement. This is a descriptive qualitative study utilizing data collection techniques such as observation, interviews, and documentation. The findings show that the hotel has well-documented SOPs, such as the "Opening Kitchen" SOP, which provides detailed instructions on kitchen equipment usage and incorporates occupational health and safety (OHS) principles. However, the implementation of SOPs in practice is not optimal due to several constraints, including staff non-compliance, lack of routine training, weak managerial supervision, and limited resources. These issues result in decreased service quality, particularly in operational efficiency and guest interaction. The study concludes that having SOPs alone is insufficient without consistent implementation and strict supervision. Therefore, improvements in training programs, periodic evaluations, and sufficient resource allocation are essential to support effective SOP enforcement.